2015
DOI: 10.1039/c5nr01420d
|View full text |Cite
|
Sign up to set email alerts
|

Design of catalytic substrates for uniform graphene films: from solid-metal to liquid-metal

Abstract: The controllable synthesis of uniform graphene with a specific layer number is crucial for both fundamental research and emerging applications due to the high sensitivity of the various extraordinary physicochemical properties of graphene to its layer numbers. However, the excessive segregation of extra C, the inactivation of the self-limiting of Cu and the superabundant nucleation at grain boundaries and defect sites render that the controllable synthesis of uniform graphene is still a challenge. By the emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 112 publications
(235 reference statements)
0
34
0
Order By: Relevance
“…On the other hand, the fluent surface enables self‐alignment of the grains into highly uniform arrays, which is beneficial for commensurate stitching . Liquid substrates are demonstrated to be extremely effective in fabricating large‐scale and high‐quality 2D materials …”
Section: Vapor‐phase Growth Of High‐quality Wafer‐scale 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the fluent surface enables self‐alignment of the grains into highly uniform arrays, which is beneficial for commensurate stitching . Liquid substrates are demonstrated to be extremely effective in fabricating large‐scale and high‐quality 2D materials …”
Section: Vapor‐phase Growth Of High‐quality Wafer‐scale 2d Materialsmentioning
confidence: 99%
“…55,[93][94][95][96] Liquid substrates are demonstrated to be extremely effective in fabricating large-scale and high-quality 2D materials. 88,97,98 Fu's group has done a series of studies on the growth behavior of 2D materials on a liquid substrate. For example, Tan et al 94 first prepared a self-aligned single-crystal array of h-BN on the surface of liquid Cu.…”
Section: Self-collimated Grains On a Liquid Substratementioning
confidence: 99%
“…discovered that single‐layered, single‐crystallinity, uniform, and large‐size graphene films can be grown on the LM surface under low and ambient pressure conditions [Figure (b, c)] . They also systematically investigated the growth mechanism [Figure (d)] ,…”
Section: The Preparation and Related Applications Of Lm Catalystsmentioning
confidence: 99%
“…Rational designing of a binary catalyst can be significant to control nucleation density, number of layers, solubility of carbon and dopant, which will provide significant control in the CVD growth process. Bilayer graphene with AA, AB stacking and rotation stacking fault is interesting prospect to observe novel physical properties (Figure 7(a)) [75][76][77]. It has been demonstrated that applying a vertical electric field in bilayer graphene-based field effect transistor (FET), a bandgap of the order of 0.2-0.3 eV can be observed [78].…”
Section: Binary Transition Metal Catalystmentioning
confidence: 99%